Effect of sand sizes on the fluidization behavior in circular and rectangular columns - Johari, Anwar; Taib, Mohamad Rozainee (Faculty of Chemical and Natural Resources Engineering, UTM, 2007)
The effect of different sand sizes on the fluidization behavior in circular and rectangular columns was investigated. Three groups of sands with different mean diameters (Sand Sieve No. 10/20 (dpmean = 0.870 mm), Sand Sieve No. 20/30 (dpmean= 0.670 mm) and Sand Sieve No. 30/60 (dpmean= 0.340 mm) were used. The. experiment was conducted using circular and rectangular columns of same the cross-sectional area. The quality of fluidization was categorized into three flow regimes, namely laminar, turbulent and slugging flow. Results showed that large particle of group D (Sand Sieve No. 10/20) provided less resistance to the bed expansion due to its physical properties and the occurrence of slugs were more pronounced. Group D particles exhibited large bubbles compared to Group B particles of Sand Sieve No. 30/60. Particles of Group B showed good fluidization behavior. Fluidization quality was affected by the column size but it does not have any effect on the shape of columns being used.